FACTORS AFFECTING THE INNOVATION ECONOMICS AND POSITION OF GEORGIA IN THE GLOBAL INNOVATION INDEX (Globalization and Business, 2023)
The article, based on the development of Georgia's innovation economics strategy, examines the factors that havea positive and negative impact on the development of innovation economics. Aim and objectives of the research: Thisarticle aims to identify the determinants affecting the development of innovation economics as well as on the basis of theimprovement of the legislative framework to create a favorable environment for the introduction of innovations, accelerateinnovation processes, improve the institutional base and achieve rapid growth in the export production of high-tech products.The article based on the analysis of innovation policies defines the role of government in improving innovation processes. Theobjective of the research is a comparative analysis of Georgia and post-soviet countries according to the Global InnovationIndex. In addition, the role of government in improving innovation processes in the country is defined based on the analysis ofinnovation policies. The impact of micro and macro factors on the innovation development of the country is highlighted. Besides, therecommendations have also been developed for creating a favorable environment for the introduction of innovations, diversifyingthe export production of high-tech products, as well as promoting both fundamental and technological research, and improving theinnovation ecosystem.